MANAJEMEN KELUHAN PELANGGAN DI RUMAH SAKIT UMUM DAERAH WONOSARI KABUPATEN GUNUNGKIDUL - , ANIK LESTARI; , dr. Mubasysyir Hasanbasri, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background:The existance ofbureaucratic reform act requires professional bureaucracy, where the role of civil servants to be public servant and competing inter part in improving the quality of the community to serve on a competitive basis. Government hospitals as a public service it is appropriate to make improvements in providing a quality service-oriented customer. One such effort is the implementation of an actual customersâ complaints management has been mandated by law No. 25 of 2009 concerning public service. But this complain are considered during a regular thing and not utilized in the efforts to improve the quality of service. So this study want to know how is customersâ complaint management and quality improvement effort because of customersâ complaint. Method:Qualitative research with case study design, conducted at Wonosari Regional Public Hospital of Gunungkidul Regency. The subject research were taken by purposive sampling for each case with 19 responden. Instrument in this study are indepth interview guide, observation reference, voice recorder, camera, and notebook. Data were collected through document review to determine case selection, interview, and observation. All of collected data is processed qualitatively. Results:Efforts to improve the quality of service because of complaints have been made even an effort of continuous improvement. In complaint handling, all of party who mix up with complaint have been involved although there was dominant role from service section. Complaints team have not work well, but complaints handling has effective enough. However, there is concern for officers already on the front-line both in the handling of complaints and improvement efforts. In controlling, there is no punishment. Punishments only in the form of guidance and direction to improvement efforts. Attitudes and behavior of workers have shown customer service oriented interest. Conclutions: In customersâ complaints management, Wonosari Regional Public Hospital has implemented TQM (Total Quality Management).The role of complaints team must be cleared and standart operating procedure need to make complaints handling more effective.